The influence of swim, cycle and run performance on overall race outcome at the off-road triathlon world championships - Hurst, H. T. (Journal of Science and Cycling, 2017)
The purpose of this study was to determine whether swim, cycle or run performance best predicts overall position during the off-road triathlon world championships. Data were collected for the top 10 finishers at each male and female world championships between 2007 and 2016. Multiple linear regression was used to predict the influence of each discipline on finishing in the top 10 overall over the 10 years, whilst one-way between subjects analysis of variance (ANOVA`s) were conducted to determine any differences in mean overall finishing time, swim, cycle and run times of the top 10 finishers between years. Cycling best predicted overall position (R2 = 0.31), followed by the run and swim (R2 = 0.17 and 0.16, respectively) for males. For females the run best predicted overall performance (R2 = 0.46), then the cycle and swim (R2 = 0.26 and 0.15, respectively). ANOVA analyses found significant differences for males in swim time (F9,99 = 4.32; p < 0.001; Etap2 = 0.30), cycle time (F9,99 = 48.33; p < 0.001; Etap2 = 0.83), run time (F9,99 = 22.89; p < 0.001; Etap2 = 0.70) and overall time (F9,99 = 59.12; p < 0.001; Etap2 = 0.86). Similarly, significant differences were also found for females in swim time (F9,99 = 3.60; p = 0.001; Etap2 = 0.26), cycle time (F9,99 = 37.14; p < 0.001; Etap2 = 0.79), run time (F9,99 = 13.77; p < 0.001; Etap2 = 0.58) and overall time (F9,99 = 28.17; p < 0.001; Etap2 = 0.74) by year. Results indicate there are differences in the influence of each discipline for males and females over the 10 years and between years. Environmental conditions and competitive background may be influential in these findings.